Islamists and the Global Order - Pfeifer, Hanna (Edinburgh University Press, 2025)
This book presents a thought-provoking challenge to the commonly held belief that Islamists uniformly reject the Western-dominated world order. In the wake of George W. Bush's declaration of a "global war on terror" in 2001, Islamists have often been associated with violence, opposition to liberal values, and the disruption of order. However, a closer examination reveals that only a fraction of the groups categorised as "Islamist" genuinely combat the global order. Through an in-depth analysis of the discourses of Tunisian Ennahda and Lebanese Hezbollah, this book demonstrates that Islamist stances toward the world order involve a delicate balance between resistance to certain aspects of the Western-dominated order and recognition of others.